Prevalence and risk of potentially adverse drug interactions in the treatment of acute alcohol poisoning - Joyce Dalline Silva Andrade; Chiara Erminia Rocha; Maria Amélia Vieira Maciel; Danielle Cristine Almeida Silva de Santana; Fernando José Malagueño de Santana
ABSTRACT The aim of this paper is to determine the profile of acute alcohol poisoning and to estimate the risk of potentially adverse drug interactions (ADIs) in patients intoxicated by alcohol when attended in emergency care at hospital. A descriptive serial cross-sectional study was performed with 4,271 individuals intoxicated by alcohol, from January 2009 to July 2011. Possible correlations were measured by Pearson's chi-square test. The data show high consumption in the population, especially in males between 25 and 59 years. The main circumstances for poisoning were alcohol misuse (96.3%). After treatment complete recovery from the signs or symptoms of the poisoning was observed in 96.88% cases; and death in 0.70%. The demonstration of potential risk for ADIs in medical care included 300 medical records which contained a history of acute alcohol poisoning. Possible drug-drug interactions (44.2%) and drug-alcohol interactions (55.8%) were demonstrated in 60.60% of analyzed medical records. Among these cases, 3%, 92.4% and 4.6% were classified as mild, moderate and severe, respectively. The measurement of ADIs aims to prevent clinical complications in medical care for alcohol misuse disorders.